Hydrothermal synthesis of reduced graphene oxide paper based nanocomposite for water treatment - Nik Mohamad, Nik Nur Amirah Farhana (2018)
A simple single-stage approach, based on the hydrothermal technique has been introduced to the synthesis of reduced graphene oxide paper based nanocomposite for water treatment. The rGO paper based nanocomposite using hydrothermal treatment are chosen as an effective way to reduce GO to rGO for the synthesis of rGO. Hydrothermal method is applied to synthesize material to produce crystalline phase, the good thermal stability of nanosized materials. GO serve as effective host material to treat water via absorption due to the presence of surface functional groups and high specific area. The nanocomposite was characterized by using X-ray Diffraction (XRD), UV-visible absorption spectra (UV-vis), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscope (SEM). The morphology of surface paper change after hydrothermal using 180°C for 24h in an autoclave. For photo catalytic activity studied by using UV- vis spectrometry. Phase identification and crystallite structure of sample determined by XRD using CuKa source radiation in a 2ϴ range 10°-80° angles and the infrared spectrum of absorption or emission of GO and rGO was determine using FTIR.